Sustainability of Water Resources for the Poor - Abulencia, James Patrick; Gallardo, Susan; Abraham, Nithin; Carracio, Anne; Ruffini, Nicholas; McDonnell, Kevin; Tañala, Francis (Consilience, 2010)
The quality of water resources for drinking water is a significant concern in many rural communities around the world. These contaminated resources directly affect natives by causing adverse health effects such as diarrhea and other gastrointestinal diseases. Potential solutions such as sand filtration, chlorination, and solar disinfection are effective technologies to purify drinking water. Another method includes reverse osmosis which is the main method for water filtration in the Philippines. However, these technologies are not feasible applications for poor communities mostly due to energy and cost concerns. To address this need for sustainable water resources, in particular for a town named Nagcarlan in the Philippines, a service learning program is proposed to employ the knowledge of engineering students to use their technical skills to serve society and thus result in personal growth. Students involved in this program have formulated a solution involving the development of a personal water filter to remove contaminants such as heavy metals using activated carbon derived from natural resources that are biodegradable and the product of recycling waste products. Sustainability of water resources is further achieved through a community outreach program with the poor communities. A successful outcome may further motivate a replication of the proposed solution to other impoverished towns within the Philippines, as well as other nations in order to service those without potable drinking water.